Bohaterstwo narodowe w kontekście świeckim i religijnym – o powiązaniach między nacjonalizmem, religią a edukacją - Hilderbrandt-Wypych , Dobrochna (Studia Edukacyjne, 2019)
A general theme of the text to discuss ideological mechanisms of non-representation of politically legitimized knowledge of underprivileged groups in the society, including women and religious or ethnic minorities in school textbooks, particularly in the area of history. Analysis of dominant views on the place of socially marginalized social groups in history textbook narratives and curricular objectives seems to be more important than ever before. Relating to Michel Foucault’s concept of discourses of truth, the aim of the text is to consider the dominant regime of truth in relation to national heroism, religion and a citizenship ideal. National heroism narratives in history textbooks are always placed is a broader context of building representations of a national identity and attempting to develop a unified notion of good citizenship. Both the nationhood and citizenship perspectives are sometimes symbolically related to the attempt of shaping emotional identification with a dominant religion.